Experiencia de aplicación del ABP para la redacción de textos argumentativos en estudiantes de la Universidad Nacional de Tumbes - Miranda Ynga, Diana Milagro (2014)
The present research investigates the application of Problem-Based Learning (PBL), as an innovative didactic methodology that propitiates, as a goal, the production of argumentative texts. The experiment was applied to students of School of Economic Sciences of the National University of Tumbes. PBL is a didactic method based in the principles of active and collaborative learning, characterized by promoting at the same time the acquisition of knowledge and attitudes. Also promotes investigation about problem solving, critical thinking, team work, communication and tolerance. In the present research, a text production development test was applied to a sample of 75 first cycle students of the National University of Tumbes. When measuring this capacity, the difference between groups (experiment and control) was compared after applying this methodology at beginning of the studies (pretest) and when concluding the experiment (posttest). Results confirmed the main hypothesis: the application of Problem-Based Learning impacts significantly in the production of argumentative texts. The posttest determined that the experimental group improved significantly this competence (28 percent with regard to their initial performance and in 23 percent in relation to the control group). The study gave evidenced that PBL is a better method to achieve text production capacity, in comparison to a traditional methodology.